The Long Term Outcome of Second Trabeculectomy with Mitomycin C after Previous Failed Operation - Yadgari, Maryam; Hassanpour, Kiana; Shahriari, Mansoor (Journal of Ophthalmic and Optometric Sciences, 2020)
Background: To evaluate the efficacy of second trabeculectomy with mitomycin C among patients with previous failed trabeculectomy. Material and Methods: This retrospective study included 23 eyes of 23 patients with failed trabeculectomy who underwent second trabeculectomy with mitomycin C at Imam Hussein Medical Center, Tehran, Iran, between January 2010 and December 2017. Pre and post operative intraocular pressure (IOP), number of medications, surgical success rate and post operative complications were recorded. The primary outcome was surgical success defined as IOP ≤ 18 mmHg according to criteria A and IOP ≤ 15 mmHg according to criteria B. Results: The mean age of patients entering the study was 54.95 ± 14.32 years. There was a significant decrease of the mean IOP post operatively at all postoperative follow ups (P < 0.001 for all follow ups) up to 2 years. Also there was a significant decrease in the mean number of IOP reducing drugs needed post operatively at all postoperative follow ups (P < 0.001 for all follow ups). The success rate per criteria A was from 96 % three months after surgery to 87 % two years after surgery. The success rate per criteria B was from 87 % three months after surgery to 74 % two years after surgery. Conclusion: Based on our results second trabeculectomy seems to be an effective method for controlling the IOP among patients with failed first trabeculectomy. Keywords: Glaucoma; Outcome; Trabeculectomy.